A Fast Algorithm for Determining the Optimal Navigation Star for Responsive Launch Vehicles - Yi Zhao; Hongbo Zhang; Pengfei Li; Guojian Tang (International Journal of Aerospace Engineering)
The platform inertial-stellar composite guidance is a composite guidance method supplemented by stellar correction on the basis of inertial navigation, which can effectively improve the accuracy of responsive launch vehicles. In order to solve the problem of rapid determining the optimal navigation star in the system, this paper proposes an algorithm based on the equivalent information compression theory. At first, this paper explains why the single-star scheme can achieve the same accuracy as the dual-star scheme. At the same time, the analytical expression of the optimal navigation star with significant initial error is derived. In addition, the available optimal navigation star determination strategy is also designed according to the arrow-borne navigation star database. The proposed algorithm is evaluated by two representative responsive launch vehicle trajectory simulations. The simulation results demonstrate that the proposed algorithm can determine the optimal navigation star quickly, which greatly shorten the preparation time before the rapid launch of vehicles and improve the composite guidance accuracy.